Communication Achieving Successful Outcomes of Inter-organizational Learning - Long, Haijiang; Kathanapha, Napaporn (เสฏฐวิทย์ปริทัศน์, 2025)
This article explores the pivotal role of communication in achieving successful outcomes in inter-organizational learning. It emphasizes that communication is the backbone of collaboration, enabling consensus-building, trust, and collective identity among members. Through various forms—ranging from informal dialogues to structured exchanges—communication fosters openness and mutual understanding, laying the groundwork for collaborative and individual learning. Effective communication not only reduces ambiguity but also aligns organizational objectives, ensuring smoother operations and improved problem-solving capabilities. The contents identify five keys factors contributing to the success of inter-organizational learning: effective communication, resource sharing, management support, trust, and shared goals. Resource sharing enhances innovation and operational efficiency by pooling diverse expertise, technologies, and knowledge, overcoming organizational silos. Management support, particularly transformational leadership, provides the vision, resources, and motivation necessary for sustained collaboration. Trust emerges as a foundational element, facilitating open knowledge exchange, reducing perceived risks, and fostering a culture of collaboration. Lastly, shared goals align the efforts of all parties, ensuring focus on mutually beneficial outcomes and long-term commitment. The findings highlight that these factors are interdependent and collectively strengthen inter-organizational learning. Trust and communication, for instance, reinforce shared goals, while resource sharing and management support enhance trust and collaboration. The study also examines the unique dynamics of social enterprises, noting how their dual pursuit of economic and social values influences inter-organizational learning and innovation. Ultimately, this research underscores that effective communication and aligned strategies are essential for transforming cooperative potential into tangible, innovative outcomes in diverse organizational contexts